2016
DOI: 10.1182/blood-2015-12-685735
|View full text |Cite
|
Sign up to set email alerts
|

Whole-exome sequencing to identify genetic risk variants underlying inhibitor development in severe hemophilia A patients

Abstract: Key Points• Exome sequencing of severe hemophilia A patients with/ without inhibitors identified rare, damaging variants in immunoregulatory genes.• Replication confirmed the association of rs3754689 in a conserved haplotype region surrounding the LCT locus with inhibitor development.The development of neutralizing antibodies (inhibitors) against coagulation factor VIII (FVIII) is the most problematic and costly complication of FVIII replacement therapy that affects up to 30% of previously untreated patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
23
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 51 publications
1
23
0
2
Order By: Relevance
“…The residual amount of endogenous FVIII offers a likely explanation for this difference, through the induction of natural immune tolerance . Furthermore, established determinants of inhibitor formation are the patient's genetic background, and environmental factors . Among them, the type of mutation in F8 is the strongest risk factor for inhibitor development .…”
Section: Introductionsupporting
confidence: 86%
“…The residual amount of endogenous FVIII offers a likely explanation for this difference, through the induction of natural immune tolerance . Furthermore, established determinants of inhibitor formation are the patient's genetic background, and environmental factors . Among them, the type of mutation in F8 is the strongest risk factor for inhibitor development .…”
Section: Introductionsupporting
confidence: 86%
“…这些因素可能造成部分HA患者在接触FⅧ制 品前血浆中就含有抗FⅧ非中和抗体, 这部分携带抗体 的患者将来替代治疗过程中更容易出现抑制物 [40] . 此 外, 关于携带抑制物患者全外显子组测序研究结果 发现多个免疫调节相关分子的有害突变及LCT基因 http://engine.scichina.com/doi/10.1360/N052017-00271 rs3754689的错义突变易导致抑制物的产生 [41] . 非遗传 因素包括外伤史、暴露日、输注剂量和药物品种及 治疗策略等.…”
Section: 研究表明 患者抑制物发生的危险因素包括遗传unclassified
“…The study found that individuals bearing the CGG or TGG haplotypes are 5.82 times more likely to develop inhibitors, whereas the CGG or TAT haplotypes appear to confer protection because they are more frequent in the group of patients without inhibitors (Chaves et al, 2010a). A genome-wide association study (GWAS) showed a protective role for the missense variant rs3754689 (C_000002.11:g.136590746C>T) in the lactase LCT gene (Gorski et al, 2016). The role of the LCT gene (i.e., hypolactasia) in the immune response remains unclear.…”
Section: Introductionmentioning
confidence: 99%